MANAJEMEN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI PERGURUAN TINGGI INSTITUT AGAMA ISLAM NURUL HAKIM KEDIRI LOMBOK BARAT - Putra, Satria (Dharmas Education Journal (DE_Journal), 2024)
Study This aims to analyze PAI learning at the Nurul Hakim Islamic Institute, Kediri, West Lombok. Using a type of field research with a descriptive approach qualitative. Data collection techniques are carried out through three techniques, namely; interviews, observations, and documentation. The research data analysis method used is an interactive model. The results of this research show that there are 4 general stages in PAI learning at the Nurul Hakim Islamic Institute. The 4 stages, namely; planning, implementation, evaluation and supervision. Regarding planning, the Nurul Hakim Islamic Institute is in the process of planning PAI learning in the National Education System, and bases itself on the vision and mission of its Higher Education. Regarding the implementation of this program, it relies on predetermined lecture times, and there are also other activities that are temporary. However, these activities did not have a significant impact on student assessments. So it can be said that the implementation of PAI learning at the Nurul Hakim Islamic Institute (IAI) is not running optimally; and related to evaluation and supervision, it was found that the evaluation and supervision carried out did not fully run optimally, as this also happened in the implementation of PAI learning at the Nurul Hakim Islamic Institute (IAI) itself.